Efektivitas Model Pembelajaran Berbasis Masalah pada Pembelajaran Gardu Induk di Sekolah Menengah Kejuruan - Khatrin Maharani; Sukardi Sukardi (Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to determine the effectiveness of the problem-based learning model in TJTL class XII substation subjects at SMK Negeri Padang. Student learning outcomes are still low caused by factors that seem monotonous learning methods. Therefore, it is necessary to do research using a problem-based learning model. This study uses a type of pre-experimental research. The design of this research is The One-Shot Case Study. According to Sumadi (2003: 100) "The One-Shot Case Study Design is the treatment given to one group of subjects, then measurements are taken. The research subject is Class XII TJTL SMK N 1 Padang consisting of two classes, namely class XII TJTL A and class TJTL B. In this study with the research theme of class XII TJTL B SMK Negeri 1 Padang Registering in the academic year 2022/2023, there are 27 students . Data collection in the study used a test instrument in the form of objective questions. Posttest data after the application of the problem-based learning model. The data obtained were analyzed using classical completeness. Based on the calculation of classical completeness, students in a class can be seen by comparing students who graduate individually or get a higher score than the school's KKM with the total number of students. Based on data analysis of 27 students, an average score of 92.59% was obtained with 25 students said to have passed and 2 students were said to have failed. Based on this score, 25 students got a higher score than the school KKM. So in terms of classical completeness learning using this problem-based learning model is very effective.